# 对数公式推导过程

## 积、商、幂的对数

$lo{g}_{a}MN=lo{g}_{a}M+lo{g}_{a}N$$log_{a}MN=log_{a}M + log_{a}N$的推导过程如下。

$\begin{array}{l}证明：设lo{g}_{a}M=p,\phantom{\rule{1em}{0ex}}lo{g}_{a}N=q\\ 则\phantom{\rule{1em}{0ex}}{a}^{p}=M,\phantom{\rule{1em}{0ex}}{a}^{q}=N，\phantom{\rule{1em}{0ex}}代入lo{g}_{a}MN，\\ 得\phantom{\rule{1em}{0ex}}lo{g}_{a}MN=lo{g}_{a}\left({a}^{p}\cdot {a}^{q}\right)=lo{g}_{a}{a}^{p+q}=p+q=lo{g}_{a}M+lo{g}_{a}N\\ 所以：lo{g}_{a}MN=lo{g}_{a}M+lo{g}_{a}N\end{array}$

$lo{g}_{a}\frac{M}{N}=lo{g}_{a}M+lo{g}_{a}N$$log_{a}{\Large\frac{M}{N}}= log_{a}M + log_{a}N$的推导过程如下。

$\begin{array}{l}证明：设lo{g}_{a}M=p,\phantom{\rule{1em}{0ex}}lo{g}_{a}N=q\\ 则\phantom{\rule{1em}{0ex}}{a}^{p}=M,\phantom{\rule{1em}{0ex}}{a}^{q}=N，\phantom{\rule{1em}{0ex}}代入lo{g}_{a}\frac{M}{N}，\\ 得\phantom{\rule{1em}{0ex}}lo{g}_{a}\frac{M}{N}=lo{g}_{a}\left(\frac{{a}^{p}}{{a}^{q}}\right)=lo{g}_{a}{a}^{p-q}=p-q=lo{g}_{a}M-lo{g}_{a}N\\ 所以：lo{g}_{a}\frac{M}{N}=lo{g}_{a}M-lo{g}_{a}N\end{array}$

$lo{g}_{a}{M}^{b}=b\cdot lo{g}_{a}M$$log_aM^b=b\cdot log_aM$的推导过程

$\begin{array}{l}证明：设lo{g}_{a}M=p\\ 则{a}^{p}=M，\phantom{\rule{1em}{0ex}}代入lo{g}_{a}{M}^{b}\\ 得lo{g}_{a}{M}^{b}=lo{g}_{a}\left({a}^{p}{\right)}^{b}=lo{g}_{a}{a}^{pb}=pb=b\cdot lo{g}_{a}M\end{array}$

${a}^{lo{g}_{a}M}=M$$a^{log_aM} = M$的推导过程

$\begin{array}{l}证明：设lo{g}_{a}M=p\\ 则{a}^{p}=M，\phantom{\rule{1em}{0ex}}代入{a}^{lo{g}_{a}M}\\ 得{a}^{lo{g}_{a}M}={a}^{lo{g}_{a}{a}^{p}}={a}^{p}=M\end{array}$

## 换底公式

$lo{g}_{b}N=\frac{lo{g}_{a}N}{lo{g}_{a}b}$$log_bN=\Large\frac{log_aN}{log_ab}$的推导过程如下。

$\begin{array}{l}证明：设lo{g}_{b}N=x，则{b}^{x}=N\\ 两边同时取以a为底的对数\\ lo{g}_{a}{b}^{x}=lo{g}_{a}N\\ x\cdot lo{g}_{a}b=lo{g}_{a}N\\ x=\frac{lo{g}_{a}N}{lo{g}_{a}b}\\ 所以lo{g}_{b}N=\frac{lo{g}_{a}N}{lo{g}_{a}b}\end{array}$

## 其他公式

$lo{g}_{{a}^{n}}a=\frac{1}{n}$$log_{a^n}a = \frac{1}{n}$的推导过程

$\begin{array}{}证明：设lo{g}_{{a}^{n}}a=p\\ 则\phantom{\rule{1em}{0ex}}\left({a}^{n}{\right)}^{p}=a即{a}^{np}=a\\ 两边同时取常数对数,\phantom{\rule{1em}{0ex}}lg{a}^{np}=lga\\ np\cdot lga=lga,\phantom{\rule{1em}{0ex}}np=1,\phantom{\rule{1em}{0ex}}p=\frac{1}{n}\\ 所以lo{g}_{{a}^{n}}a=\frac{1}{n}\end{array}$

$\frac{1}{lo{g}_{a}b}=lo{g}_{b}a$${\Large \frac{1}{log_ab}} = log_ba$的推导过程。

$\frac{1}{lo{g}_{a}b}=\frac{1}{\frac{lgb}{lga}}=\frac{lga}{lgb}=lo{g}_{b}a$

$lo{g}_{{a}^{n}}M=\frac{1}{n}\cdot lo{g}_{a}M$$log_{a^n}M = {\Large \frac{1}{n}} \cdot log_aM$的推导过程

$证明：设lo{g}_{a}M=p\phantom{\rule{0ex}{0ex}}则{a}^{p}=M，代入lo{g}_{{a}^{n}}M\phantom{\rule{0ex}{0ex}}lo{g}_{{a}^{n}}{a}^{p}=p\cdot lo{g}_{{a}^{n}}a=\frac{1}{n}\cdot p=\frac{1}{n}\cdot lo{g}_{a}M$